Levantamentos de pesquisas, experiências e formação de professores - Alencar, Edvonete Souza de; Cunha, Aldrin Cleyde da; Figueiredo, Tiago Dziekaniak; Miola, Adriana Fatima de Souza (TANGRAM - Revista de Educação Matemática, 2020)
--